THU0366 Efficacy of Adalimumab in Patients with Axial Spondyloarthritis: Results of an Investigator-Initiated 12-Weeks Randomized Double-Blind Placebo Controlled Trial with a 12 Weeks Open-Label Extension Phase. (23rd January 2014) - Pedersen, S. J.; Sørensen, IJ; Loft, AG; Hindrup, JS; Thamsborg, G; Asmussen, K; Kluger, E; Nørregaard, J; Christensen, TG; Jurik, AG; Møller, JM; Hasselquist, M; et al.
Abstract : Objectives: To investigate the efficacy of adalimumab in patients with axial spondyloarthritis (SpA). Methods: In this randomized double-blind placebo-controlled trial, 52 patients with axial SpA were allocated to adalimumab 40 mg or placebo subcutaneously every other week for 12 weeks, followed by an open label extension phase of 12 weeks, where all patients received adalimumab. Patients were included if they had 1) SpA according to the ESSG criteria; 2) sacroiliitis on MRI and/or X-rays; 3) BASDAI ≥40 mm despite treatment with NSAIDs. The primary clinical endpoint was a reduction in BASDAI of ≥50% or 20 mm (BASDAI response) and secondary endpoints were ASAS20 and ASAS40 responses. Results: 27 patients (21 male (78%), median age 41 years (range 23-65), 26 (96%) HLA-B27 positive, disease duration 13 years (1-35), BASDAI 60 mm (IQR: 50-68), CRP 10 mg/l (range: 1.6-50)) were treated with adalimumab 40 mg every other week, and 25 patients (19 (76%) male, age 37 years (23-54), 17 (77%) HLA-B27 positive, disease duration 6 years (1-25), BASDAI 62 (46-72), CRP 5.3 mg/l (1.2-131)(all NS) were treated with placebo. 46 (88%) patients completed weeks 12 and 24. Patients were excluded because of increased disease activity (n=2; placebo), multiple sclerosis (n=1; placebo), infection (n=1; adalimumab) and violation of protocol (n=2; adalimumab/placebo). All patients were excluded before week 12. At week 12, significantly more adalimumab-treated than placebo-treated patients reached an ASAS40 response (p=0.04), whereas numerically more adalimumab-treated patients achieved a BASDAI (48% versus 24%, p=0.07) and ASAS20 (63% vs. 44%, p=0.17) response. Very high responder rates (BASDAI response rates ≥80%) were seen at week 24 in both groups. Conclusions: Adalimumab is clinically effective for treatment of patients with axial spondyloarthritis. The high response rate may be explained by the patients being younger and with shorter disease duration. Disclosure of Interest: S. J. Pedersen Grant/research support from: Research support